With the Implementation of the VAT Law Postponed, What Additional Domestic Revenue Mobilization Measures Could Be Considered? : Bangladesh Policy Note - World Bank (World Bank, Washington, DC, 2018)
The postponement of 2012 VAT Law implementation means that the higher tax revenues expected from the measure will be delayed, and additional sources of revenue need to be considered. Model simulations suggest that implementation of the VAT Law starting July 1, 2017 at the originally proposed rate of 15 percent would have yielded additional tax revenue of about 1 percent of GDP in FY2018, and 0.8 percent of GDP in FY2019. Several measures could be considered to make up this short-fall. Automation and process simplification could bring additional tax revenues ranging from 0.3 to 0.7 percent of GDP in FY2018. There is substantial scope for efficiency gains in shifting from a type-of-tax towards a function-based tax administration, facilitating compliance. Carbon taxes could generate resources equivalent to 1 percent of GDP, and tobacco taxes could raise a further 1 to 2 percent of GDP. Rationalizing tax incentives and exemptions can also generate more revenue. The proposed administrative measures, including expanding tax withholding mechanisms, would not require legislative changes and could be implemented in the short term, boosting revenue during the current fiscal year (FY2018). The other tax policy measures could be considered for implementation in the medium term and would require corresponding legislative initiatives.